2015
DOI: 10.1007/s10544-015-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Acoustophoretic removal of proteins from blood components

Abstract: This work presents the development of a miniaturized system for removing plasma proteins and other low-molecular-weight compounds from red blood cell (RBC) concentrate in a simple one-step-process using integrated ultrasound. The technology utilizes the principles of acoustophoresis to transfer the RBCs from the original plasma-containing solution into a protein-free SAG-M additive solution in a continuous flow process. The preparation of protein free RBC concentrate is important for blood transfusion to patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…Tenje et al 57 were achieved in this work which were found to rise to even higher values upon increasing the acoustic radiation intensity. Unlike multi-laminar stream devices used for washing particles and protein removal from blood samples, the device used in this study has only one inlet, decreasing the risk of accuracy loss occurred due to the mismatch of acoustic properties in the channel.…”
Section: Acoustic Particle Manipulationsupporting
confidence: 51%
“…Tenje et al 57 were achieved in this work which were found to rise to even higher values upon increasing the acoustic radiation intensity. Unlike multi-laminar stream devices used for washing particles and protein removal from blood samples, the device used in this study has only one inlet, decreasing the risk of accuracy loss occurred due to the mismatch of acoustic properties in the channel.…”
Section: Acoustic Particle Manipulationsupporting
confidence: 51%
“…The use of acoustic waves to purify blood cells from lipids, bacteria, and even from other blood cells has been demonstrated for a decade using flow rates of mL/h [13][14][15]. In general, the use of acoustics for separating cells is more efficient and less damaging to the cells, with separation efficiencies approaching 97% with minimal to no hemolysis [2,15]. However, the technology was limited by these flow rates, which were hundreds of fold lower than what would be considered clinically relevant for surgical procedures or even blood banking.…”
Section: Discussionmentioning
confidence: 99%
“…In the proposed separation the presence of blood cells and plasma proteins in the sample increases the acoustic impedance of the sample stream relative to a regular buffer and hence the sample will relocate to the centre outlet without any separation (Fig. 1c ) 49 , 52 . In the current study the relocation of the sample stream was prevented by increasing the acoustic impedance of the central medium to match the acoustic impedance of 20% whole blood.…”
Section: Separation Considerationsmentioning
confidence: 99%